Small-scale landfills: impacts on groundwater and soil - Bellezoni, Rodrigo Augusto [UNESP]; Iwai, Cristiano Kenji; Elis, Vagner Roberto; Paganini, Wanderley da Silva; Hamada, Jorge [UNESP] (Springer, 2014)
In Brazil, the large quantities of solid waste produced are out of step with public policies, technological developments, and government budgets for the division. In small municipalities, the common lack of technological knowledge and financial conditions for suitable waste disposal has resulted in a large number of illegal dumps. Therefore, small sanitary landfill facilities are working with simplified operations focusing on cost reduction and meeting the economic and technological standards of the city without endangering the environment or public health. Currently, this activity is regulated at a federal level although there is some uncertainty regarding the risk of soil and aquifer contamination as theses facilities do not employ liners. Thus, this work evaluates a small landfill to identify changes in soil and groundwater using geotechnical parameters, monitoring wells, and geophysical tests performed by electrical profiling. It is verified that based on current conditions, no contaminants have migrated via underground water aquifers, and overall no significant changes have occurred in the soil. It is concluded that, despite its simplicity, the method investigated is a viable alternative for the final disposal of municipal solid waste from small cities, especially in developing countries.
Keywords: Final disposal; Municipal solid waste; Soil investigation; Monitoring